1973
DOI: 10.1152/ajplegacy.1973.224.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heart work and insulin on glycogen metabolism in the perfused rat heart

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, post-prandial elevations in circulating factors such as insulin are anticipated to promote glucose uptake and utilization by the heart, resulting in increased rates of glycolysis and glucose oxidation during the awake period (relative to the sleep phase), which persist in the ex vivo setting [28, 38]. A dichotomy exists for glycogen turnover, wherein increased cardiac work promotes glycogenolysis, while insulin stimulates glycogen synthesis [36, 39, 40]. However, it has been reported that in the heart net glycogen synthesis occurs during the active period (when cardiac work is increased), while net glycogenolysis occurs during the sleep phase [38].…”
Section: Time-of-day-dependent Changes In Myocardial Metabolismmentioning
confidence: 99%
“…Similarly, post-prandial elevations in circulating factors such as insulin are anticipated to promote glucose uptake and utilization by the heart, resulting in increased rates of glycolysis and glucose oxidation during the awake period (relative to the sleep phase), which persist in the ex vivo setting [28, 38]. A dichotomy exists for glycogen turnover, wherein increased cardiac work promotes glycogenolysis, while insulin stimulates glycogen synthesis [36, 39, 40]. However, it has been reported that in the heart net glycogen synthesis occurs during the active period (when cardiac work is increased), while net glycogenolysis occurs during the sleep phase [38].…”
Section: Time-of-day-dependent Changes In Myocardial Metabolismmentioning
confidence: 99%
“…However, in our experiments, hearts were equilibrated with [3~]glucose and insulin for =50 min before inducing ischemia. Thus, a sufficient time was allowed for incorporation of labeled glucose into glycogen and for the perfusate glucose radioactivity to equilibrate with that of the endogenous glucose pool (34,35). This issue, however, deserves additional investigation.…”
Section: Discussionmentioning
confidence: 99%